Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Pada Klinik Kecantikan Puspita Cabang Kotabumi - Tri Lestiraputri Warganegara; Devi Alviyani (Universitas Mitra Indonesia, 2020)
AbstractThe problems formulated are, Does Product Quality affect Customer Loyalty, Does Service Quality affect Customer Loyalty, Does Product Quality and Service Quality simultaneously affect Customer Loyalty. The purpose of this research is to determine the effect of product quality on customer loyalty, to determine the effect of service quality on customer loyalty, to determine the effect of product quality and service quality together on customer loyalty. The sample in this study were consumers at the Puspita Beauty Clinic Kotabumi Branch, amounting to 100 respondents. Data collection used a questionnaire. The method used is multiple linear regression. The results of this study are Product Quality Affects Customer Loyalty at Puspita Beauty Clinic, Kotabumi Branch, Service Quality Influences Customer Loyalty at Puspita Beauty Clinic Kotabumi Branch, Product Quality and Service Quality Affects Customer Loyalty at Puspita Beauty Clinic, Kotabumi Branch. Keywords: Product Quality, Service Quality, Customer Loyalty